2005
DOI: 10.1242/dev.01973
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of placodes: a molecular genetic investigation of the larvacean urochordate Oikopleura dioica

Abstract: The evolutionary origin of vertebrate placodes remains controversial because divergent morphologies in urochordates, cephalochordates and vertebrates make it difficult to recognize organs that are clearly homologous to placode-derived features, including the olfactory organ, adenohypophysis, lens, inner ear, lateral line and cranial ganglia. The larvacean urochordate Oikopleura dioica possesses organs that morphologically resemble the vertebrate olfactory organ and adenohypophysis. We tested the hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 82 publications
3
76
1
Order By: Relevance
“…Implicated respectively in the development of major tissues and sensory organs, their origin is generally correlated with the increase in morphological complexity of vertebrates. However, recent molecular developmental studies have revealed the presence in tunicates of migratory neural crest-like cells (Jeffery, 2006;Jeffery et al, 2004) and olfactory placodes (Bassham and Postlethwait, 2005;Mazet et al, 2005). When reinterpreted in light of the new chordate phylogeny, these results implied that both of these features did not evolve de novo in the vertebrate lineage, but rather evolved from specialized pre-existing structures in the common ancestor of vertebrates and tunicates.…”
Section: Implications For Chordate Evo-devomentioning
confidence: 98%
“…Implicated respectively in the development of major tissues and sensory organs, their origin is generally correlated with the increase in morphological complexity of vertebrates. However, recent molecular developmental studies have revealed the presence in tunicates of migratory neural crest-like cells (Jeffery, 2006;Jeffery et al, 2004) and olfactory placodes (Bassham and Postlethwait, 2005;Mazet et al, 2005). When reinterpreted in light of the new chordate phylogeny, these results implied that both of these features did not evolve de novo in the vertebrate lineage, but rather evolved from specialized pre-existing structures in the common ancestor of vertebrates and tunicates.…”
Section: Implications For Chordate Evo-devomentioning
confidence: 98%
“…A cluster of cells with club-shaped cilia in the cerebral vesicles is the only possible balance organ known in amphioxus (Lacalli, 2004). Molecular markers suggest that atria in urochordates represents potential candidate of mechanosensory organs orthologous to the otic placode (Bassham and Postlethwait, 2005). The homology of atria with otic placodes remains questionable because their sensory cells are different from those in vertebrates (Lacalli, 2004).…”
Section: Paired Otic Capsule Is Lacking In Early Crest Animalsmentioning
confidence: 99%
“…Molecular and morphological data are accumulating in attempts to clarify the evolution of neurogenic placodes and neural crest; however, at the moment, there is no agreement on their interpretation. (3)(4)(5)(29)(30)(31) Evidence for the existence of migratory neural crest cells has so far been reported only in tunicates. (2) Taking advantage of the large size of Ecteinascidia turbinata embryos, it was firstly found possible to follow cells migrating from the dorsal midline into the larval trunk and entering the oral and atrial siphon primordia, gut and body wall, where some of them differentiated into pigmented cells.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the rostral, stomodeal and neurohypophysial placodes, responsible for the formation of sensory palps, neural gland and cerebral ganglion, were hypothesized to possess cell populations homologous to the olfactory/adenohypophysial placodes and hypothalamus. (3)(4)(5)43) Of particular interest are the stomodeal and neurohypophysial placodes, which have a primary role in the formation of the neural complex.…”
Section: Introductionmentioning
confidence: 99%